Refinement Types for Secure Implementations - Bengtson, Jesper; Bhargavan, Karthik; Fournet, Cédric; Gordon, Andy; Maffeis, Sergio (IEEE Computer Society, 2008)
We present the design and implementation of a typechecker for verifying security properties of the source code of cryptographic protocols and access control mechanisms. The underlying type theory is a λ-calculus equipped with refinement types for expressing pre- and post-conditions within first-order logic. We derive formal cryptographic primitives and represent active adversaries within the type theory. Well-typed programs enjoy assertion-based security properties, with respect to a realistic threat model including key compromise. The implementation amounts to an enhanced typechecker for the general purpose functional language F#; typechecking generates verification conditions that are passed to an SMT solver. We describe a series of checked examples. This is the first tool to verify authentication properties of cryptographic protocols by typechecking their source code.
20th IEEE Computer Security Foundations Symposium (CSF) 2008